Endogenous Cushing syndrome from an ectopic adrenocorticotropic hormone production as a rare cause of ocular hypertension - Khaw, K.W.; Jalaludin, M.Y.; Suhaimi, H.; Harun, F.; Subrayan, V. (Elsevier, 2010)
Ocular hypertension caused by endogenous Cushing syndrome from an ectopic adrenocorticotropic hormone producing tumor is rare. We report an 11-year-old boy who presented with intraocular pressures (IOPs) of 50 mm Hg in both eyes. Surgical resection of the tumor was performed with subsequent normalization of serum cortisol and IOP levels.